Modeling the Green Transition in the European Union: An Organic Market-Oriented Perspective - Veghes, Călin; Dima, Andreea Strâmbu; Stoenică, Laurentiu (European Journal of Sustainable Development, 2025)
In the context created by the short-term energy market disruptions generated by the war in Ukraine and the longer-term concern for achieving a climate-neutral continent by 2050, the European Commission issued, in May 2022, the REPowerEU plan aiming to reduce significantly the dependence on fossil-based energy sources by 2027. Despite the increasing employment of renewables, the green transition faced important challenges and did not generate results consistent with the proposed objectives. The nature of the transitional process explains the gap between objectives and results suggesting that an organic transition to clean sources of energy could be a more effective strategy allowing a gradual reduction of the share of the still important conventional sources in energy production and final consumption and their corresponding balanced replacement with renewables ones. The paper presents the results of an exploratory assessment based on the secondary data and from a market-oriented perspective of the evolution of final energy consumption and energy production structures, weighing the shares of renewables and conventional energy in the last three decades, regarded as the background of the future modeling attempts, in connection to the relevant economic, social, and environmental dimensions of the sustainable development in the EU Member States. Keywords: Green transition, Renewable energy, Energy market, European Union, Sustainable development